Systematic review of strategies for rural tourism regeneration in the post-epidemic era-the case of mainland China - Sun, Yichen; Li, Mingxuan; Liu, Yu (International Journal of Asian Social Science, 2023)
This paper aims to summarise the methods of rural tourism revitalization in the post-epidemic period in the existing literature and screen out the strategies suitable for China. The method of subject analysis and the stakeholder theory are adopted as the main approaches to achieve the goal by analysing the methods to help rural tourism development from four dimensions: local government, local community, travel agency, and residents. According to China’s conditions and experience from other countries, the paper finally puts forward four strategies for China’s rural tourism regernation. Specifically, for the government, the accessible strategies are to provide low-interest loans to tourism practitioners, for communities, it is proper to help scenic spots install disinfection facilities. Considering the travel agencies, to develop Virtual Reality (VR) and Augmented Reality (AR) programs could help, and residents in rural tourism destinations can participate in the environmental protection to help the revitalisation. The practical significance of this study is mainly to provide theoretical basis for the development direction of rural destinations in China in the post-epidemic period. At the same time, other countries with similar situation to China’s rural tourism can also make selective reference. Despite the problems of a single database and neglect of regional differences within China, the research results still have particular value.